Tinjauan Klinis CADASIL (Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy) - Danar Dwi Anandika (PT Kalbe Farma Tbk., 2021)
CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) adalah penyakit herediter langka dengan prevalensi 4,14 per 100.000. Penyakit ini disebabkan mutasi gen Notch 3 pada kromosom 19. Manifestasi klinisnya bervariasi dengan onset gejala awal migrain dengan aura. Pada tahap lanjut akan dijumpai lesi infark multipel di area subkortikal. Pasien juga dapat mengalami gangguan psikiatri dan neurobehaviour. Tidak ada terapi kausal, dapat diberikan terapi simptomatik. CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy) is a rare hereditary disease with a prevalence of 4.14 per 100,000. The disease is caused by a mutation of the Notch 3 gene on chromosome 19. The clinical manifestations vary with the onset of initial symptoms is migraine with aura. In advanced stages, there will be multiple infarct lesions in the subcortical area. Patients may also experience psychiatric and neurobehavioral disorders. There is no causal therapy, only symptomatic therapy.